Effects of Expired and Non-Expired Pendimethalin and Hand Weeding on the Bio- Productivity and Seed Quality of Groundnut (Arachis Hypogaea L.) - Lawal, Amudalat; Olayinka, Bolaji; Ayinla, Abdulaziz; Alabi Bulala, Fauzat; Muktar, Sodi; Abdulra’uf, Lukman (Science Journal of University of Zakho, 2023)
The use of expired herbicides to suppress weeds growth is becoming prevalent among farmers. Hence the need to investigate and compare the effect of expired and non-expired pendimethalin and hand weeding on weed suppression, growth, yield and composition of groundnut. The experiment was carried out during therainy season in 2020. It consisted of seven weed control treatments. These were sole pendimethalin non-expired (T1), pendimethalin non-expired + one hand weeding at 6 weeks after sowing (T2), pendimethalin expired (T3), pendimethalin expired + one hand weeding at 6 WAS (T4), two hand weeding at 3 and 6 WAS (T5), weed free check (T6) and weedy check (T7). Desmodium trifolium, Amaranthus spinosusand Commelina benghalensis were the most preponderant weedspecies. Both expired or non-expired pendimethalin and their integration with one hand weeding reduced weed population than other treatments. Pendimethalin non-expired + one hand weeding at 6WAS and two hand weeding at 3 and 6 WAS significantly increased the growth parameters and yield when compared with other treatments. In this study, two hand weeding at 3 and 6 WAS and non-expired pendimethalin + one hand weeding 6 WAS, should be reinforced for weed control on account of their positive influence on groundnut productivity and seed quality.